De novo mutations in the gene encoding the synaptic scaffolding protein SHANK3 in patients ascertained for schizophrenia - Gauthier, Julie (National Academy of Sciences, 2010)
Schizophrenia likely results from poorly understood genetic and environmental factors. We studied the gene encoding the synaptic protein SHANK3 in 285 controls and 185 schizophrenia patients with unaffected parents. Two de novo mutations (R1117X and R536W) were identified in two families, one being found in three affected brothers, suggesting germline mosaicism. Zebrafish and rat hippocampal neuron assays revealed behavior and differentiation defects resulting from the R1117X mutant. As mutations in SHANK3 were previously reported in autism, the occurrence of SHANK3 mutations in subjects with a schizophrenia phenotype suggests a molecular genetic link between these two neurodevelopmental disorders.